EFFECT OF ADDITION OF VERMICOMPOST, BIO AND MINERAL FERTILIZER ON THE AVAILABILITY OF SOME NUTRIENTS IN SOIL AND POTATO YIELD - Abdul-Ratha, ALmamori & (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
A nitrogenous bio-fertilizer comibination was prepared contain Azospirillum lipoferum, and Azotobacter chroococcum bacteria. A phosphate bio-fertilizer consisting of Bacillus megaterium and Glomus mosseae fungus was also prepared. vermicompost was produced from earthworms imported from Iran and others isolated locally. A factorial experiment was carried to evaluate the effect of the interaction between these combinations and vermicompost types under levels of 0%, 25% and 50% of NPK. The results showed a significant superiority of the bio-fertilizer (nitrogen and phosphate) treatment in available nitrogen in the soil after harvest, number of tubers, yield per plant , and the total yield with 39.70 mg N kg -1, 11.03 tuber plant -1, 1367.40 g plant-1, and 43.76 Mg ha-1 respectively. While phosphate bio fertilizer treatment giving available phosphorus in the soil by 22.74 Mg P kg -1 , vermicompost produced from imported earthworms was superior in giving available phosphate in the soil with value 22.74 mg p kg -1 . While the tri interaction was superior for all studied characteristics.